The Communicative Role of the Addressee in Artistic Communication: Specific Features of Expression (Linguostylistic Studies, 2019)
The article highlights the communicative positions of the speaker and the addressee in the inner-text communication with an emphasis on the communicative role of the speaker and addressee in the text of fiction and how it is realized in the specific speech acts. The communicative role of the addressee is implemented by such types of recipients: a speaker (addresser); listener (addressee); indirect (secondary) addressee as an active participant of communication and observer as a passive participant of communication. Most communicative roles are related to the addressee. The communicative role of the addressee "splits" in the text into four types of communicative roles, depending on the degree of participation of the addressee in communicative interaction. The dialogical form of communicative interaction focuses on the communicative roles of the speaker and the listener. The speaker puts the question, hears the answer and generalizes the heard. Under such conditions, the speaker (addresser) is the initiator of the conversation, his communicative role is characterized by an active position, he introduces the topic, directs the communication, guides the listener in conversation. The addressee is also an active participant in communicative interaction, he not only listens to the speaker, but also answers the question, determines the further development of communication. Indirect (secondary) addressee is present during communicative interaction, therefore, he may interfere with the conversation, though he does not act as a direct addressee ( the speaker's replies are not addressed to him). The communicative role of the recipient-observer is realized in those cases, when the focus of attention in the conversation is changed, "moves" from one participant of communication to another, that is, there is a shift in communicative roles. An observer as a passive participant of communication is only indicated in the artistic text as a character present during the communicative interaction, but he does not participate in the conversation. Key words: сommunicative role, speaker, addressee, linguistic personality, intra-textual communication. SourcesAndrukhovych, Yurii. Moskoviada. Roman zhakhiv. Ivano-Frankivsk : Lileia-NV, 2000.Dashvar, Liuko. Krov z molokom. Kharkiv : Knyzhkovyi klub “Klub simeinoho dozvillia”, 2008.Zhadan, Serhii. Depesh Mod. Kharkiv : Folio, 2004.Izdryk, Yurii. AMTM. Novely. Lviv : Kalvariia, 2005.Irvanets, Oleksandr. Zahalnyi analiz. Kharkiv : Folio, 2010.Kozhelianko, Vasyl. Defiliada v Moskvi. Lviv : Kalvaria, 2008.Pokalchuk, Yurii. Anatomiia hrikha. Kharkiv : Folio, 2008.Shkliar, Vasyl. Zalyshenets. Chornyi voron. Kharkiv : Knyzhkovyi klub “Klub simeinoho dozvillia”, 2010.Yatsenko, Petro. Povernennia prydurkiv. Lviv : Kalvariia, 2004.  ReferencesBahtin, Mihail. Jestetika slovesnogo tvorchestva. Moskva : Iskusstvo, 1979.Karasik, Vladimir. Jazykovyj krug: lichnost', koncepty, diskurs. 2nd ed. Moskva : Gnozis, 2004.Karaulov, Jurij. Russkij jazyk i jazykovaja lichnost'. Moskva : Nauka, 1987.Krasnyh, Viktorija. ”Svoj” sredi “chuzhih”: mif ili real'nost'? Moskva : Gnozis, 2003.Formanovskaja, Natal'ja. Rechevoe obshhenie: kommunikativno-pragmaticheskij podhod.  Moskva : Russkij jazyk, 2002.